2005
DOI: 10.1055/s-2005-869834
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasound in the Synthesis of 2-(Alkylamino)benzoic Acids in Water

Abstract: The synthesis of substituted 2-(alkylamino)benzoic acids using the Ullmann condensation with water as the solvent and utilizing ultrasound irradiation was achieved with high yields in a short reaction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Early reports concerning Ullmann reactions in water or aqueous media appeared in the early 2000s, 226,227 but it was only around the years 2006-2009 that this field saw an expansion. A discussion on previous work can be found in another review.…”
Section: Reactions In Watermentioning
confidence: 99%
“…Early reports concerning Ullmann reactions in water or aqueous media appeared in the early 2000s, 226,227 but it was only around the years 2006-2009 that this field saw an expansion. A discussion on previous work can be found in another review.…”
Section: Reactions In Watermentioning
confidence: 99%
“…In general, by using DMF the yields in the condensation of primary amines were significantly improved and the reaction time was reduced dramatically relative to those with water as the solvent. [15] For secondary amines (Table 1, Entries 1b-20b), we achieved moderate coupling yields (50-71 %); this can be ascribed to the enhanced steric hindrance of the secondary amines relative to the primary amines. In the case of secondary acyclic amines (Table 1, Entries 13b-20b), the yields obtained were higher than (51-57 %) those reported for this coupling.…”
Section: Resultsmentioning
confidence: 88%
“…In a previous publication, [15] we analyzed the influence of some parameters on the condensation of 2-chlorobenzoic acid and substituted primary alkylamines in water as the solvent to yield the corresponding 2-(alkylamino)benzoic acids. It was observed that the reaction of 3 wt.-% of copper, 2.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Robin and co-workers successfully synthesized acridine derivatives using this method (Robin, M., et al, 2002). In order to replace dry organic solution with more environmentally benign ones: Pellon et al extended the synthesis of halobenzoic acid and alkylamine in the presence of water as a solvent with copper under probe sonication (Pellon, R. F., et al, 2005 ). In most cases the yields were 20% greater than those resulting from classic heating.…”
Section: Fig (14)mentioning
confidence: 99%